Case Report: SARS-CoV-2 Gamma Isolation From Placenta of a Miscarriage in Midwest, Brazil - Fernandez, Zoraida; Lichs, Gislene G. C.; Zubieta, Claudia S.; Machado, Ana B.; Ferreira, Mia A.; Valente, Natalia; Keren, Thayssa; Arantes, Ighor; Nacife, Valeria; Pereira, Elisa Cavalcante; Appolinario, Luciana; Lacerda, Thays E. J.; et al. (Frontiers in Medicine, 2022)
The present study investigated a SARS-CoV-2 infection in placenta and fetal samples from an early pregnancy miscarriage in Midwest Brazil. The Gamma variant was isolated and fully sequenced from the placenta sample, but not from fetal samples. Our findings highlight potential adverse perinatal outcomes caused by SARS-CoV-2 Gamma infection during pregnancy.